1982
DOI: 10.1159/000238077
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Comparative Activity of Moxalactam, GR 20263, and N-Formimidoyl Thienamycin to Other Beta-Lactam Antibiotics and Tobramycin against Enterobacteriaceae and Staphylococci

Abstract: The in vitro activities of moxalactam, GR 20263, and N-formimidoyl thienamycin were compared to those of cephalothin, cefazolin, cefamandole, cefoxitin, and tobramycin against 152 strains of Enterobacteriaceae and staphylococci. The results showed that moxalactam, GR 20263, and N-formimidoyl thienamycin each had significantly improved activity toward the gram-negative organisms tested compared to the other β-lactams and tobramycin. N-formimidoyl thienamycin was particularly impressive with respect to its activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1984
1984
1987
1987

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The third generation cephalosporins and moxalactam have been suggested as potential single agents for broad spectrum antimicrobial therapy but extensive clini cal studies documenting this indication have not been carried out [2]. Our data showed that either cefoperazone, cefotax ime or moxalactam inhibited 95% of 148 Enterobacteriaceae at an M IC^ 1.6 ug/ml and suggest that these agents might well be effective in community hospital infections with these organisms.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…The third generation cephalosporins and moxalactam have been suggested as potential single agents for broad spectrum antimicrobial therapy but extensive clini cal studies documenting this indication have not been carried out [2]. Our data showed that either cefoperazone, cefotax ime or moxalactam inhibited 95% of 148 Enterobacteriaceae at an M IC^ 1.6 ug/ml and suggest that these agents might well be effective in community hospital infections with these organisms.…”
Section: Discussionmentioning
confidence: 64%
“…Species of bacteria and number of each (in paren theses) included E. coli (78), K. pneumoniae (26), K. oxytoca (5), E. aerogenes (7), E. agglomerans (l), E. cloacae (9), P. mirabilis (8), P. rettgeri (2), M. morganii (1), S. flexneri (1), S. marcescens (3), C. freundii (1), C. diversus (2), Salmonella, group D (1), Salmo nella group B (2), Salmonella, group C (1), P. aerugi nosa (16), P. cepacia (3), P. pseudoalcaligenes (1) and A. calcoaceticus (2). Gordon/Tack/Haddy/Fechner/Wofford…”
Section: Methodsmentioning
confidence: 99%